The impact of human resource management, learning, and academic infrastructure in pre-service teachers on pedagogical competence: A multifaceted analysis - Sunismi Sunismi; Mochamad Imron Azami; Fitri Awaliyatush Sholihah; Mohammad Badrih (Association for Scientific Computing Electrical and Engineering(ASCEE), 2024)
This study investigated the influence of the learning process, human resources, and infrastructure on the pre-service teachers' competencies, particularly their pedagogical competence as future professional teachers. This study employed survey research, a type of quantitative investigation. The study's population consisted of all 182 Pre-Service Teachers from the Indonesian Language and Literature Education Department, Mathematics, and English Education Department of the Teacher Professional Education Program, Faculty of Teacher Training and Education, Universitas Islam Malang. Primary and secondary data were the two data types used in this investigation: questionnaires and documentation. The main source of information was the assessment of the lecture process in Batches 1 and 2 of the Pre-Service Teacher of Teacher Professional Education Program. The course grades from LMS courses taken by pre-service PPG students made up the secondary data. Based on the results and discussion, it can be concluded that the learning process and human resources positively influenced the pre-service teacher's competence, especially in the pre-service teacher professional education program. Meanwhile, the data showed that academic infrastructure did not impact pre-service teacher competence.